2012
DOI: 10.1371/journal.pone.0049699
|View full text |Cite|
|
Sign up to set email alerts
|

Economic Burden of Human Papillomavirus-Related Diseases in Italy

Abstract: IntroductionHuman papilloma virus (HPV) genotypes 6, 11, 16, and 18 impose a substantial burden of direct costs on the Italian National Health Service that has never been quantified fully. The main objective of the present study was to address this gap: (1) by estimating the total direct medical costs associated with nine major HPV-related diseases, namely invasive cervical cancer, cervical dysplasia, cancer of the vulva, vagina, anus, penis, and head and neck, anogenital warts, and recurrent respiratory papil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
45
0
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(54 citation statements)
references
References 42 publications
5
45
0
4
Order By: Relevance
“…Similar models have been previously applied in many studies and searches in the field of health economics evaluation [13][14][15][16][17][18][19][20][21][22] to represent a 1-year static estimation of the economic burden due to disease.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar models have been previously applied in many studies and searches in the field of health economics evaluation [13][14][15][16][17][18][19][20][21][22] to represent a 1-year static estimation of the economic burden due to disease.…”
Section: Methodsmentioning
confidence: 99%
“…The review allowed systematising the available information, but this may not be representative of the real practice on a national level. To fill this gap, the Open Access model proposed a well-validated probabilistic estimate method, [13][14][15][16][17][18][19][20][21][22] considering the variability in the literature as minimum and maximum range in which it was highly possible to obtain the real inference estimate.…”
Section: Statistical Analysesmentioning
confidence: 99%
“…The annual cost in Italy of the treatment of genital warts is approximately € 37 million for females and about € 33 million for males (55). An economic analysis showed that the costs associated with GWs in men and women represented 24.3% (€ 70.9 million) of the total costs associated with HPV-6,-11,-16 and -18 diseases in Italy; preventing GWs and the associated costs alone would cover most of the costs for qHPV vaccination (55).…”
Section: Anogenital Wartsmentioning
confidence: 99%
“…Estimated cost per case of AGW ranged from US$124 per case in a patient seen for care in Canada25 to US$883 per case in Spain 34. AGW management costs were derived from information collected from case note reviews (13 papers),18–22 25 26 28 29 31–34 expert opinion (3 papers),16 24 35 surveillance data (3 papers)17 23 27 or the literature (1 paper) 30…”
Section: Resultsmentioning
confidence: 99%
“…Six papers reported management cost for anal cancers,30 36–40 but half of these were annual treatment costs,37 39 40 not cost per case. Cost per anal cancer case ranged from US$12 936 (Italy30) to US$51 571 (Denmark36). Twelve reported head and neck cancer treatment costs and differed depending on cancer site and stage,30 37 41–50 with costs ranging from US$6912 (laryngeal cancer, T1 carcinoma, The Netherlands48) to US$52 579 (weighted average costs for cancers of the oral cavity, larynx or oropharynx, The Netherlands45).…”
Section: Resultsmentioning
confidence: 99%